A facile design of azaanthracene derivatives: ACQ–AIE conversion and blue-shifted mechanofluorochromic emission. (February 2021) - Huang, Mingming; Lu, Hao; Wang, Kun; Liu, Beibei; Wang, Meng; Qiao, Xiaoyao; Yang, Jiping
Abstract: Azaanthracene derivatives, e.g. phenoxazine and phenothiazine, have attracted considerable interest not only in chemistry but also in materials science for the unique electron structures and photophysical properties. However, like most organic luminogens, phenoxazine and phenothiazine both suffer from the annoying aggregation-caused quenching (ACQ) effect, which greatly limits their further application in solid state conditions. Fortunately, the discovery of aggregation-induced emission (AIE) phenomenon provides an elegant platform to solve the stubborn ACQ effect. But most of the existing AIEgens have been prepared through some complicated synthesis processes, which are commonly unpopular with environmental unfriendly, high cost, and low solubility. Therefore, it deserves great attention to explore a simple and cost effective approach to achieve the AIE modification of phenoxazine and phenothiazine. In this work, two diphenylethylene substituted azaanthracene derivatives DPE-POZ and DPE-PTZ were masterly designed and synthesized through a fairly simple one-step reaction. The introduction of multi-rotor group diphenylethylene endows the products with twisted molecular conformations, which successfully promotes the photophysical behavior conversion of ACQ-AIE. The αAIE (the ratio of PL intensity in a mixed solvent with 90 vol% fraction of water to 0 vol%)of DPE-POZ and DPE-PTZ reached 8 and 23, respectively. In addition, DPE-POZ exhibited an uncommon blue-shifted mechanofluorochromic phenomenon. The powder X-ray diffraction and single crystal X-ray diffraction characterizations revealed that the MFC properties could be attributed to the phase transition between the crystalline and amorphous states which was promoted by the loose solid molecular arrangement. Graphical abstract: Azaanthracene-based enamine derivatives DPE-POZ and DPE-PTZ have been designed and synthesized through a simple one-step method to achieve the conversion of ACQ-AIE, of which DPE-POZ exhibits an uncommon blue-shifted mechanofluorochromic behavior. Image 1 Highlights: Azaanthracene derivatives DPE-POZ  and DPE-PTZ  have been designed and synthesized through a simple and cost effective method. The introduction of diphenylethylene moiety successfully realized the conversion of ACQ-AIE of phenoxazine and phenothiazine. DPE-POZ  exhibits an uncommon blue-shifted mechanofluorochromic phenomenon. Different solid-state photophysical behaviors of DPE-POZ  and DPE-PTZ  are studied by PXRD and SCXRD experiments.